RMB resilience strategies to drive business performance amid the global crisis - Zheng, Yingrong; Dong, Hao; Milojevic, Marko (Journal of Business Economics and Management, 2023)
The purpose of this article is to examine the impact of RMB exchange rate fluctuations on the strategic decisions of Chinese companies in the context of their export activity in the foreign market. The research methodology is based on integrated annual customs data for the period 2014–2021 and econometric analysis. The upward fluctuations in the level of the real effective exchange rate of the RMB encourage companies to withdraw from foreign markets and lead to a significant slowdown in companies’ export market entry. At the same time, companies with foreign capital are able to cope with currency risks to a much greater extent than companies with state and private participation. The analysis of company characteristics based on the principle of differentiation shows that company performance, profit volume, business scale, and export experience of a company can lead to a delay in the favorable effect of RMB appreciation for companies leaving export markets. This article provides valuable guidance for companies on strategies to avoid currency risks and make effective management decisions in the context of exports. First published online 18 January 2024